The Impact of Direct Environment on Children Socialization as Consumers - Goupilleau, Virginie (2006)
This study aims to investigate the impact of the environment, namely media, parents, peers and authority figure outside the family nest, on the process of socialization of children as consumers. A lot of studies have been done in this domain by focusing on their cognitive and social development, and their information processing abilities. These frameworks appear to be out of date and need to be updated as children appear to develop these abilities and skills much earlier nowadays than the previous generations. Using a qualitative research method, the aim is to conduct an exploratory study in France, interviewing children from 7 to 11 years old, in order to provide a basis of comparison and to contrast the results with previous research. A framework is therefore proposed taking into account the previous research, namely the children inner development capacity, and the external forces that have an impact on children socialization as consumer as a multiplication and differentiation factor. This view allows having a more dynamic perspective on this process and aim to explain why children are now more developed as consumer than previous generations. This study is helpful to both academicians and practitioners as it is going to provide some a new basis of analysis taking into account the changing environment and a full insight of the children socialization phenomenon.